Martin Fotta a Paloma Gay y Blasco (eds.) Ethnographic Methods in Gypsy, Roma and Traveller Research: Lessons from a Time of Crisis: Bristol: Bristol University Press, 2024, 177 s., ISBN 978-1-5292-3186-8 - Šotola, Jaroslav (Romano džaniben, 2024)
RECENZE